La condición jurídica de la mujer en la tradición: “El divorcio de la condesita” - Rodríguez Chávez, Iván (2018)
Ricardo Palma in the tradition The divorce of the little countess, presents literarily the legal framework of the woman, in her condition of daughter under her father’s authority until her condition of wife under the husband’s authority, which she gets to outwit avoiding the co-habitational consummation of marriage with a strategy that let her leave the conjugal house, take refuge in a convent and interpose him a divorce lawsuit; a conflict that ends with her husband’s death. As a widow, she leaves the monastery, with the fortune of the inheritance.